An experimental study of the (Ti–6Al–4V)–xH phase diagram using in situ synchrotron XRD and TGA/DSC techniques. (1st February 2015) - Sun, Pei; Fang, Z. Zak; Koopman, Mark; Paramore, James; Chandran, K.S. Ravi; Ren, Yang; Lu, Jun
Abstract: Hydrogen has been investigated for decades as a temporary alloying element to refine the microstructure of Ti–6Al–4V, and is now being used in a novel powder metallurgy method known as "hydrogen sintering and phase transformation". Pseudo-binary phase diagrams of (Ti–6Al–4V)–xH have been studied and developed, but are not well established due to methodological limitations. In this paper, in situ studies of phase transformations during hydrogenation and dehydrogenation of (Ti–6Al–4V)–xH alloys were conducted using high-energy synchrotron X-ray diffraction (XRD), thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The eutectoid phase transformation of β ↔ α + δ was observed in the (Ti–6Al–4V)–xH alloy via in situ synchrotron XRD at 211 °C with a hydrogen concentration of 37.5 at.% (measured using TGA–DSC). The relationships of hydrogen composition to partial pressure and temperature were investigated in the temperature range 450–900 °C. Based on these results, a partial pseudo-binary phase diagram of (Ti–6Al–4V)–xH is proposed for hydrogen compositions up to 60 at.% in the temperature range 100–900 °C. Using the data collected in real time under controlled parameters of temperature, composition and hydrogen partial pressure, this work characterizes relevant phase transformations and microstructural evolution for practical titanium–hydrogen technologies of Ti–6Al–4V.